IL-15 induced bystander activation of CD8+ T cells may mediate endothelium injury through NKG2D in Hantaan virus infection - Zhang, Xiyue; Zhang, Yusi; Liu, He; Tang, Kang; Zhang, Chunmei; Wang, Meng; Xue, Manling; Jia, Xiaozhou; Hu, Haifeng; Li, Na; Zhuang, Ran; Jin, Boquan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Hantaan virus (HTNV) can cause endothelium injury in hemorrhagic fever with renal syndrome (HFRS) patients. Bystander activation of CD8+ T cells by virus infection has been shown that was involved in host injury, but it is unclear during HTNV infection. This project aimed to study the effect of bystander-activated CD8+ T cell responses in HTNV infection. Methods The in vitro infection model was established to imitate the injury of endothelium in HFRS patients. Flow cytometry was performed to detect the expression of markers of tetramer+ CD8+ T cells and human umbilical vein endothelial cells (HUVECs). The levels of interleukin-15 (IL-15) in serum and supermanant were detected using ELISA kit. The expression of MICA of HUVECs was respectively determined by flow cytometry and western blot. The cytotoxicity of CD8+ T cells was assessed through the cytotoxicity assay and antibody blocking assay. Results EBV or CMV-specific CD8+ T cells were bystander activated after HTNV infection in HFRS patients. HTNV-infected HUVECs in vitro could produce high levels of IL-15, which was positively correlated with disease severity and the expression of NKG2D on bystander-activated CD8+ T cells. Moreover, the elevated IL-15 could induce activation of CD122 (IL-15Rβ)+NKG2D+ EBV/CMV-specific CD8+ T cells. The expression of IL-15Rα and ligand for NKG2D were upregulated on HTNV-infected HUVECs. Bystander-activated CD8+ T cells could exert cytotoxicity effects against HTNV-infected HUVECs, which could be enhanced by IL-15 stimulation and blocked by NKG2D antibody. Discussion IL-15 induced bystander activation of CD8+ T cells through NKG2D, which may mediate endothelium injury during HTNV infection in HFRS patients.